Override Parade: Isu-Isupariwisata Berkelanjutanpada Destinasi Kepulauan di Indonesia - Putu Diah Sastri Pitanatri (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2019)
Tourism today has a problem. It is addicted to growth, which is incompatible withsustainability goals. Despite three decades of discussing pathways to sustainable tourism,tourism authorities worldwide has continued to promote tourism growth despite the ecologicaland social limits of living on a finite planet. Looking to it’s case to an island destination inIndonesia overtourism and tourism leakage are two major problems the industry arefacing. Therefore this article argues that tourism must be understood and managed with awider context of sustainability. Additionally, strategic approaches to transitioning to asufficiency approach to tourism and leisure is essential if sustainability is to be secured.Recommendations include Sustainable Mobilities, fostering diverse approaches to tourismstrategies for development and regulating and managing tourism. An upgraded reseach insustainable mobility through big data is recommended to further diverse tourism strategiesfrom approach, that be analyzed in real-time and directly targeted at tourism and destinationproblems